Selected Topics on Enablers for Next-Generation Information Systems Development: Editorial Introduction to Issue 25 of CSIMQ - Robert Andrei Buchmann (Complex Systems Informatics and Modeling Quarterly)
The 25th issue of CSIMQ presents four articles that investigate novel enablers for information systems development. Three of the selected articles focus on conceptual modeling methods, whereas the fourth one investigates the readiness of SMEs for Industry 4.0 adoption. Model-driven engineering was both tailored (on method level) and applied in two of the papers, taking a Design Science approach to develop proofs-of-concept for the notion of “technology-specific modeling”, a particular flavor of domain-specific modeling – more precisely, technology-specific modeling languages reflect the specificity of a technological ecosystem or pattern (e. g. REST APIs, MVC Web development frameworks). The third paper's contribution may also be seen as a modeling method, although it is not framed as such – it focuses on a design viewpoint and its theoretical applicability in business scenarios. This method proposes a chemistry-inspired technique for optimizing enterprise collaboration patterns based on their KPI effects. Finally, the last paper takes a systematic literature review approach to investigate Industry 4.0 adoption at SME level through the lens of a modified version of the IMPULS assessment model.